Moderasi Beragama dalam Situs tafsiralquran.id - Muhammad Miftahuddin; Fatikhatul Faizah; Arif Kurniawan (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2020)
Abstract: The case of intolerance between religious communities is still a sexy thing to study, considering that there are still many cases of intolerance between religious communities in Indonesia. One of the causes is the understanding of religious exclusivity and the lack of moderation of thought - especially in understanding the holy texts - in society. So here it becomes important to put forward the reasoning of moderation in viewing the verses of the holy book, in order to create good relations between religious communities. In the current era, online media has become a key media for spreading thoughts on understanding religiousness. This paper will discuss how the moderation makes sense regarding the relationship between religious communities in one of the most influential interpretation sites, namely tafsiralquran.id. The selection of the site was due, first, to the emphasis on the contextuality aspect of the tafsiralquran.id site content. So that it always follows developing issues, especially in Indonesia. Second, tafsiralquran.id is one of the websites that focuses its content on the activities of interpreting the al-Qur'an, which is rarely found in other websites which mostly discuss the interpretation of the al-Qur'an only on a particular theme or topic. The results of this study conclude that the inter-religious conception of moderation is described in seven dimensions of religious moderation which are equipped with indicators, namely; moderation in the aspects of theology, worship, muamalah, law, creation of man and the universe, government and culinary. The seven dimensions of moderation are highly relevant to the context of Indonesian society which is plural, heterogeneous and multiethnic.